Prototyping, Customer Involvement and Speed Information Dissemination in New Product Success - Tih, Siohong; Wong, Kok Kee; Gary, S. Lynn; Richard, R. Reilly (Emerald Group Publishing Limited, 2015)
Purpose Rapid prototyping can potentially accelerate the entire process of new product development (NPD), enabling a high level of customer involvement and hence new product success (NPS). This study aims to examine the relationship between prototyping and NPS, and the moderating effect of customer involvement, as well as the influence of speed of information dissemination on customer involvement.